2021
DOI: 10.3390/ani11082294
|View full text |Cite
|
Sign up to set email alerts
|

Lameness in Early Lactation Is Associated with Lower Productive and Reproductive Performance in a Herd of Supplemented Grazing Dairy Cows

Abstract: The main aim of this study was to assess the associations between the timing of lameness clinical case occurrence in lactation with productive and reproductive performances in grazing Holstein cows. A cohort study was carried out on a dataset with records from a commercial dairy herd (Buenos Aires, Argentina) for cows that calved and were dried off from January 2010 through June 2017. The first recorded event of lameness per lactation was considered for the study. Criteria for lactation inclusion included not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…The study by L o g r o ñ o et al [34] showed a poor correlation between lameness and milk production, a reduced probability of service and pregnancy, and prolonged calving to conception delay. This is mostly caused by intense discomfort and pain, which reduces the severity of agitation symptoms and releases pro-inflammatory mediators that alter behaviour, resulting in an energy deficit [4,8,9,23].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The study by L o g r o ñ o et al [34] showed a poor correlation between lameness and milk production, a reduced probability of service and pregnancy, and prolonged calving to conception delay. This is mostly caused by intense discomfort and pain, which reduces the severity of agitation symptoms and releases pro-inflammatory mediators that alter behaviour, resulting in an energy deficit [4,8,9,23].…”
Section: Discussionmentioning
confidence: 96%
“…Milk production cannot be optimal without reproducing, due to physiological interactions, between lactation, and reproduction [2]. Performances in reproduction, and productivity, significantly impact dairy farmers' economic success [34]. These tasks require proper management and monitoring [22].…”
Section: Introductionmentioning
confidence: 99%
“…Production diseases such as lameness influence the welfare and sustainability of dairy herds, resulting in long-term negative effects on milk yield, fertility, and the need to cull dairy cows [ 8 , 36 , 74 ]. This is a challenging aspect when considering dairy production in the tropics, where major factors such as economic restrictions, a lack of agricultural politics, and a lack of availability of robust scientific information already limit the ability to sustainably manage a dairy herd’s health.…”
Section: Discussionmentioning
confidence: 99%